Gender, Sharia, and Public Sphere: Women Navigating Qanun in Aceh’s Coffee Shop Culture - Khori Suci Maifianti; Sarwititi Sarwoprasodjo; Rilus A Kinseng; Dwi Sadono; Sarah P Cardey (Journal Public Policy, 2026)
This study aims to examine how women in Aceh navigate Sharia-based moral regulations within the gendered public sphere of coffee shop culture and to analyze the strategies they employ to construct agency, identity, and visibility under Qanun governance. Using a descriptive phenomenological approach, this research adopts Judith Butler’s theory of gender performativity as its main analytical framework. Data were collected through semi-structured interviews and participant observation involving five active female informants in coffee shops in West Aceh. The findings indicate that women’s participation in coffee shop culture represents adaptive and strategic forms of everyday agency. Women negotiate religious and social boundaries by regulating their presence through specific choices of visiting time, clothing, seating positions, and interaction styles, allowing them to remain within socially acceptable norms while subtly challenging gendered exclusions. Furthermore, coffee shops function as informal yet significant arenas for gender contestation, enabling women to build professional networks, engage in public discourse, and consolidate social and professional agendas in traditionally male-dominated spaces. In conclusion, the study demonstrates that the public sphere in Aceh simultaneously reflects Sharia control and opens opportunities for women to exercise adaptive and subversive agency. These findings contribute to the literature on gender relations, Sharia regulation, and public space by highlighting coffee shops as micro-level sites where women continuously negotiate identity, rights, and participation in a post-conflict society governed by religious norms.